Lets Talk Mediterranean 06 Paul Love - The Mediterranean Seminar (2021)
Mediterranean Seminar co-directors, Brian Catlos and Sharon Kinoshita, interview Paul Love, whose “Provenance in the Aggregate: The Social Life of an Arabic Manuscript Collection in Naples” was the Mediterranean Seminar's Article of the Month for April 2021.
Keywords: Manuscrits -- Naples

Naples MS ARA 50 | مخطوط رقم ٥٠ في جامعة نابولي - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2017)
Keywords: Manuscrits -- Naples

Ibadi MSS at the Univ. of Naples "L'Orientale" | المخطوطات الإباضية في جامعة نابولي الشرقية - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2014)
Keywords: Manuscrits -- Naples

Ibadi Manuscripts in Naples| المخطوطات الإباضية في نابولي - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2017)
I am delighted to announce that I have now posted an inventory and catalog of the Ibadi manuscripts held at the Special Collections Library of the Università degli Studi di Napoli L’Orientale in Na…
Keywords: Manuscrits -- Naples

Catalog of Ibadi Manuscripts at the Special Collections Library of the Università degli Studi di Napoli L’Orientale فهرس المخطوطات الإباضية في مكتبة الكتب النادرة في جامعة نابولي "الشرقية" - Love Jr, Paul M. (2017)
Keywords: Catalogue -- Naples; Manuscrits -- Naples

Provenance in the Aggregate: The Social Life of an Arabic Manuscript Collection in Naples - Love Jr, Paul M. (Manuscript Studies: A Journal of the Schoenberg Institute for Manuscript Studies, 2018)
Keywords: Manuscrits -- Naples